(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In world linguistics today, the paradigm of anthropocentric humanism, the idea of man having his own thoughts and feelings, is important, and historical consciousness is the highest spiritual value of man. Therefore, the systematic consideration of the phraseological fund of a particular national language and the formation of phrases is of particular importance in a more precise sense - in the reflective function of "historical memory". The identification of archaic phraseological units representing "historical memory" attracted the attention of linguists, especially at the beginning of the century. This problem has been widely studied in foreign linguistics, which has been studied on the basis of different theories, concepts, approaches, positions, directions.